Green synthesis of stabilized spherical shaped gold nanoparticles using novel aqueous Elaeis guineensis (oil palm) leaves extract - Ahmad, T. (Elsevier B.V., 2018)
In the last decade, development of bioinspired protocols to synthesize gold nanoparticles (AuNPs) using plants and their extracts have been dealt by researchers due to their low cost, renewability and non-toxic features. A simple, cheap and ecofriendly method is reported to synthesize stabilized AuNPs of size 35â75 nm at room temperature using aqueous Elaeis guineensis (oil palm) leaves extract without addition of any external agent. Oil palm leaves mediated AuNPs were characterized using FTIR, UVâvis spectrophotometer, EDAX, XPS, FESEM, TEM, DLS and TGA. FTIR spectra results revealed contribution of phenolic, carboxylic, amines and amides in reduction of trivalent gold ions and stabilization of formed gold atoms. Reaction solution color change and UVâvis spectra confirmed reduction of gold ions to generate gold atoms. Reaction mechanism explained the role of phenolic compounds in reduction reaction using FTIR and UVâvis spectra results. EDAX and XPS results further validated the formation of metallic gold particles through bioreduction of gold ions. Crystal structure of metallic gold particles was confirmed through XRD peaks indexing to (111), (200), (220) and (311) planes. TEM and FESEM particles size measurements exhibited the formation of nanostructured AuNPs. Synthesis of well scattered and spherical shaped AuNPs was revealed through FESEM and TEM images. The excellent stability of AuNPs was shown through high negative zeta potential value (â14.7 Â± 4.68 mV) and uniform dispersion in aqueous media. Our results disclosed the excellent potential of Elaeis guineensis (oil palm) leaves as reducing and stabilizing agents in green synthesis of well scattered spherical shaped AuNPs, which can be employed as strong candidates in medical drug delivery and industrial applications. Â© 2017 Elsevier B.V.